Rancang Bangun Perangkat Eksperimen Hukum Archimedes untuk MTs LB/A Yaketunis Kelas VIII - Rofiqoh Utami; Winarti Winarti; Joko Purwanto (INKLUSI, 2014)
Blind students find difficulties whenever they are involved in the experiment of Archimedes principle as it requests an active visual role. Thus, it is very important to design a special tool for blind students so their practice of Archimedes principle become easier. This paper discusses a research finding which is an innovation of adaptive tools for blind students, such as beaker glass with Braille number, dynamometer with modification and Braille number (Braille Spring Balance) and recording lesson about Archimedes principle. This research done for students MTs LB / A Yaketunis Class VIII which aims at analyzing the quality of each tool by media experts, lesson experts, and physics teacher of MTs LB/A.This research is R & D with procedural models adapted from the development of the 4-D models, namely Define, Design, Develop, and Disseminate. According to media expert assessment, beaker glass with Braille number and Braille spring balance has a very good quality with percentage of their respective 100% of the ideal score, while the assessment by lesson experts for each tool have a good quality with percentage 80% and 73.33% of the ideal score, and physics teacher of MTs LB / A assessment for each tool have a very good quality with percentage 100%. According to the media and lesson experts, the recording lesson about Archimedes principle have a good quality with percentage 80% of the ideal score, according to physics teacher MTs LB / A, the recording tool has excellent quality either with percentage 91.82% of the ideal score. This research recommends the blinds students to utilize these innovative-adaptive tools which will enable them appropriately practice Archimedes principle as non-blind students.